Giant Cicada Emergence, Protandry and Chorus Centers Formation as Revealed by Studies Using a Sound Trap - Andrade, Samuel de Carvalho [UNESP] (2017)
The giant cicada, Quesada gigas (Olivier) (Hemiptera: Cicadidae), is an important coffee pest and information about the behavior and reproduction of this species, e.g. emergence, senescence and ovarian maturation status, can be valuable to understand giant cicada ecology and to improve the use of a sound trap as a control method. A great number of Q. gigas adult males and females was captured using a sound trap and a protandrous type of emergence possibly associated with chorus centers formation was observed. All giant cicadas collected until 14–15 days after the beginning of male emergence (DAME) had immature ovaries at two different years of evaluation. On the other hand, the majority of cicadas collected from 20 until 48 DAME had mature ovaries with visible chorionated oocytes. Despite the use of the sound trap to collect insects for ecological studies, we believe that next generations of Q. gigas can be reduced by using this sound trap to hinder the formation of giant cicada chorus centers, to reduce male availability to copulate with females and to reduce the number of females to oviposit in coffee plants.